The Influence Of Social Media Influencers On Purchase Intentions Mediated By Affinity, Brand Image, Loyalty, And Trust In Erigo Products Among Tiktok Users In Indonesia - Dedi Iskamto; Pahmi Ahmad Faruk (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (Adpebi), 2026)
This study examines the influence of social media influencers on purchase intention for Erigo products, considering the mediating role of affinity, brand image, trust, and loyalty. Data were obtained from 280 respondents of TikTok users in Indonesia through a digital survey, and analysed using Smart PLS 4.0. The results show that homophily, social presence, and physical attractiveness of influencers significantly influence purchase intention. Affinity, brand image, trust, and loyalty act as partial mediators that strengthen the relationship between these variables. Homophily or similarity between the influencer and the audience increases Affinity and Trust, while social presence creates a strong emotional connection. In addition, the physical attractiveness of the influencer strengthens the appeal of the marketing message. This study highlights the importance of the emotional connection between consumers and influencers (affinity) in shaping purchase behaviour. Companies are advised to select influencers that match the brand's values and target market, as well as focus on building Trust, creating a strong social presence, and increasing customer Loyalty.TikTok, with rapid user growth, is becoming a strategic platform for influencer-based marketing. Its interactive characteristics allow brands like Erigo to effectively reach a wider audience. This research contributes to the digital marketing literature by uncovering TikTok's unique dynamics in influencer marketing strategies, particularly in the Indonesian fashion industry.